When Every Second Counts: Novel Device to Shorten Chest Tube Insertion Time in a Pre-hospital Setting. Issue 2 (December 2016) - Drori, Ariel; Kan-tor, Yoav; Nadorp, Bettina; Goldstein, Chen; Buxboim, Amnon; Nahmias, Yaakov; Levy, Liran
Abstract Tension pneumothorax is a life-threatening medical emergency mostly associated with chest trauma. It is considered a leading cause of death due to injury and represents a substantial portion of potentially preventable deaths in the battlefield. The accepted therapeutic approach is manual thoracostomy with chest tube insertion. This is a relatively simple procedure when performed by skilled hands and in optimal conditions. In the battlefield and in other pre-hospital settings or when performed by unprofessional personnel, it may become complicated and time-consuming. We describe a novel technique for the treatment of pneumothorax in the pre-hospital setting, utilizing a quick, one-handed, easy-to-apply approach.